2010
DOI: 10.1007/s12011-010-8613-5
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Modifies the Effect of Short-Term Chilling Stress on Cucumber Plants

Abstract: The objective of this study was to investigate the effect of selenium (Se) supply (0, control; 2.5, 5, 10, or 20 μM) on cucumber (Cucumis sativus L.) cv. Polan F1 plants grown under short-term low temperature stress. About 14-16 day-old seedlings, grown at an optimal temperature (25/20°C; day/night), were exposed to short-term chilling stress with a day/night temperature of 10°C/5°C for 24 h, for a further 24 h at 20°C/15°C, and then transferred to 25/20°C (re-warming) for 7 days. Se did not affect the fresh w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…Understanding the biochemical and molecular responses to salt stress is essential for the holistic perception of plant resistance mechanisms under salt stress. Recent studies have shown that, at low concentrations, Se can protect plants from several types of abiotic stress by enhancing the antioxidant capacity [14,16,31]. In this study, we investigated the possible regulatory role of exogenous Se on ascorbate (AsA) and glutathione (GSH) content; the activities of the AsA-GSH cycle; and the glyoxalase system enzymes, including glutathione S-transferase (GST), glutathione peroxidase (GPX), and catalase (CAT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the biochemical and molecular responses to salt stress is essential for the holistic perception of plant resistance mechanisms under salt stress. Recent studies have shown that, at low concentrations, Se can protect plants from several types of abiotic stress by enhancing the antioxidant capacity [14,16,31]. In this study, we investigated the possible regulatory role of exogenous Se on ascorbate (AsA) and glutathione (GSH) content; the activities of the AsA-GSH cycle; and the glyoxalase system enzymes, including glutathione S-transferase (GST), glutathione peroxidase (GPX), and catalase (CAT).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified several beneficial effects of selenium (Se) for plants, even though Se is not considered to be a requirement for higher plants [12]. Some research groups have reported that Se cannot only promote growth and development of plants, but also increase resistance to certain abiotic stresses, e.g., salinity [13,14], drought [15], chilling [16], toxic metals [17], and UV irradiation [18]. Se exerts beneficial effects on the growth and stress tolerance of plants by enhancing the antioxidant capacity [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Se at low concentrations can protect plants from several types of abiotic stresses (Hawrylak-Nowak et al, 2010 ;Valadabadi et al, 2010).Temperature stress (high temperature) can cause premature leaf senescence which leads to loss of chlorophyll, increased membrane damage and progressive decline in photosynthetic capacity (Djanaguiraman et al, 2009). High temperature stress directly damages the photosynthetic apparatus and decreases both photosynthetic rate and duration of the assimilate supply (Prasad et al, 2008; (Srivalli and Khanna-Chopra, 2004).…”
Section: Seleniummentioning
confidence: 99%
“…Selenium (Se) can prevent oxidative damage to body tissues (Lobanov et al, 2008) because of its structural role in synthesis of glutathione peroxidase enzyme. Se can also increase tolerance of plants exposed to low temperature (Hawrylak-Nowak et al, 2010), drought stress (Valadabadi et al, 2010) and aluminum toxicity (Cartes et al, 2010). Djanaguiraman et al (2005) …”
Section: Seleniummentioning
confidence: 99%
“…For the past couple of decades, the beneficial role of Se in plants has been reported, but the question is still unresolved whether Se is an essential micronutrient for plants. Some plant species supplemented with Se have also shown enhanced tolerance to certain abiotic stresses like salinity [15,16], drought [17], extreme temperature [18,19], metal toxicity [20,21], and UV radiation [22]. There is evidence for the role of Se in enhancing the cellular antioxidant machineries in plants which resulted in the detoxification of ROS [23].…”
Section: Introductionmentioning
confidence: 99%